ORIENTASI MORAL DENGAN PENDEKATAN KEAGAMAAN DALAM SUPERVISI PENDIDIKAN AGAMA ISLAM - Adabi, Husni (Program Studi Magister Pendidikan Agama Islam Universitas Hasyim Asy’ari Tebuireng Jombang m Asy'ari, 2022)
Educational supervision plays an important role in improving the quality of learning and enhancing teachers’ professionalism in carrying out educational processes. In the context of Islamic Religious Education, supervision functions not only as an administrative control mechanism but also as a means of moral and spiritual guidance for educators. This study aims to analyze the moral orientation in the supervision of Islamic Religious Education through a religious approach. The research employs a literature study method with a descriptive-analytical approach to various scholarly sources related to educational supervision, moral education, and Islamic education. The data were collected from books, journal articles, and other relevant academic documents, which were systematically analyzed to understand the concept and implementation of a religious approach in educational supervision. The findings indicate that supervision in Islamic Religious Education should be directed toward comprehensive teacher development encompassing pedagogical, moral, and spiritual dimensions. A religious approach in supervision enables supervisors to integrate Islamic values into the guidance process so that learning activities are not limited to cognitive achievement but also contribute to students’ character formation. Furthermore, moral development in Islamic education requires the integration of three essential components: moral knowledge, moral feeling, and moral action, which are interconnected and mutually reinforcing. Therefore, educational supervision grounded in religious values can serve as an effective strategy for improving educational quality while fostering students’ moral character holistically.